2018
DOI: 10.1093/ecco-jcc/jjy186
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Human Milk Metabolome, Cytokines, and Antibodies in Inflammatory Bowel Diseases Versus Healthy Mothers, and Potential Impact on the Newborn

Abstract: Background and Aims: For women with inflammatory bowel disease [IBD], it is not very well known how IBD or IBD treatment affects their breast milk components. We aimed to investigate whether breast milk composition differs in healthy control [HC] versus IBD mothers in terms of antibodies, cytokines, and metabolite,s to identify potential impact of IBD breast milk on neonatal immune system. Methods: Breast milk specimens from HC [n = 17] and IBD [n = 31 for Crohn's disease [CD]; and n = 41 for ulcerative coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 71 publications
2
45
0
Order By: Relevance
“…Acetate, butyrate, and formate have been found in HM of women worldwide (20)(21)(22)(23)(24)(25)(26) (20)(21)(22). We also confirm the positive correlations of HM acetate with butyrate and formate reported by Prentice et al The failure by us and others to detect propionate in HM is curious.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Acetate, butyrate, and formate have been found in HM of women worldwide (20)(21)(22)(23)(24)(25)(26) (20)(21)(22). We also confirm the positive correlations of HM acetate with butyrate and formate reported by Prentice et al The failure by us and others to detect propionate in HM is curious.…”
Section: Discussionsupporting
confidence: 88%
“…Butyrate has also been documented in studies of HM fat or fatty acids ( 23 , 24 ). Meng et al reported the presence of acetate and butyrate in HM from women with and without irritable bowel disease, finding higher acetate levels in women treated with aminosalicylates ( 25 ). Finally, Gómez-Gallego et al performed NMR metabolic profiling of 79 HM samples from 4 international cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…In some of the included publications the type of biologic used was not specified for the outcomes. In general, these studies did not show any abnormal outcomes in children exposed to biologics during pregnancy/lactation [155][156][157][158][159][160][161][162][163][164][165][166][167].…”
Section: Biologics (In General Not Specified)mentioning
confidence: 99%
“…Furthermore, these samples could also be used to determine whether the immune and metabolic profile of breastmilk differs in women with and without chronic conditions. 57 Once additional data are available for mAb transfer into breastmilk when used in neurologic disorders, this should be incorporated into treatment guidelines in neurology. While awaiting additional studies, data presented here may provide some reassurance for low mAb transfer to breastmilk, although study of breastmilk transfer of individual therapies and effects on children is needed.…”
Section: Discussionmentioning
confidence: 99%